Demokrasi, Governance, dan Oligarki: Konglomerasi Media MNC Group Keterlibatannya Melancarkan Capres Ganjar Pranowo Pada Pemilu 2024 - Hawa Shofurani (Politeia: Jurnal Ilmu Politik, 2024)
This article discusses the issue of the MNC group as oligarchic media and the news it displays only appears to be based on political interests. The media oligarchy influences political contestation, the latest political reality shows that the Perindo Party supports presidential candidate Ganjar Pranowo in the 2024 presidential election and also utilizes television media as a political capital and political campaign infrastructure in the 2024 presidential election. This research aims to explore the phenomenon of the MNC Group media conglomeration which siding with the coalition of presidential candidate Ganjar Pranowo to form an oligarchy that can influence the governance system. This research adopted a qualitative research design and data collection was carried out through literature reviews from various journals and online publications of articles related to this issue. Research findings show that the MNC Group as the media broadcaster broadcasts broadcasts on television only for political purposes, this has resulted in a democratic crisis because the media no longer has independence, and this phenomenon states that there is a media oligarchy in Indonesia which makes Indonesia bad governance. The research results contribute to a better understanding of democracy, media oligarchy, and cultural hegemony in political media.